Phenotypic differentiation and genetic diversity of Saccharomyces cerevisiae strains from vineyards of the Azores Archipelago - Neves, J. Drumonde (2012)
This work aims to evaluate diversity of Saccharomyces cerevisiae strains from vineyards of the Azores Archipelago and to estimate the degree of phenotypic and genetic differentiation among geographically isolated islands. During two consecutive years, 163 grape musts were obtained from grape samples collected in eight islands of the Archipelago, that belonged to traditional (Arinto, Verdelho and Terrantez) and hybrid grape varieties. The sampling plan included vineyards in appellations of origin and abandoned vineyards. Ninety-four spontaneous fermentations were achieved. From the final fermentative stages, 2670 yeast isolates were obtained. The species identification was performed by restriction fragment length polymorphism analysis (RFLP) and sequencing of ITS regions. S. cerevisiae strains delimitation was performed by interdelta sequences analysis. S. cerevisiae strains were phenotypically evaluated regarding the combined resistance to ethanol/SO2, ß-glucosidade activity, H2S production and the killer/sensitive phenotype. From all isolates collected, 22.2% belonged to non-Saccharomyces species and 77.8% to S. cerevisiae, which were classified in 284 strains. We found phenotypic variations among strains according to their origin (islands, grape variety or vineyard management). Fifty percent of S. cerevisiae isolates from Graciosa, the island with the largest area of contiguous vineyards, showed killer activity, whereas this value was considerably lower in the other six islands (0 – 12 %). On this island we also found a high genetic diversity, since the average number of S. cerevisiae strains per fermentation was of 6.4 and 6.7 on the islands Graciosa and Santa Maria, respectively. Lower values (ranging between 1.2 and 4.9) were observed in each of the other five islands. On each island of the Azores Archipelago, S. cerevisiae isolates from abandoned vineyards tended to be less resistant to SO2 (100 ppm) in comparison with strains obtained from cultivated vineyards. Sequencing of genetically most distinctive strains is currently underway.